Navigobius kaguya, new species of ptereleotrine goby (Teleostei: Gobiidae) from the West Pacific - Gill, Anthony C.; Tea, Yi-Kai; Senou, Hiroshi (Zootaxa, 2017)
Navigobius kaguya is described on the basis of two specimens from the Ryukyu Islands, Japan, and Luzon, Philippines. It differs from other described species of the genus in live coloration, and in having: second dorsal-fin rays I,16; anal-fin rays I,16; pectoral-fin rays 21–22; gill rakers 5–6 + 17; and first dorsal fin weakly to moderately incised between spines, taller than second dorsal. It closely resembles an undescribed species from Bali and the Maldives, but differs in lacking an orange-red mid-lateral stripe. The possible placement of Navigobius khanhoa in Oxymetapon is discussed.